Hubungan Kadar Kolesterol Dengan Trigliserida Pada Pasien Hipertensi di UPTD Laboratorium Kesehatan Daerah Kota Jambi - Karwiti, Witi; Umizah, Larasti Putri; Kurniasih, Dewi; Rezekiyah, Sholeha; Lestari, Wuni Sri; Aprianti, Andra Delvi (Jurnal Kesehatan Komunitas, 2024)
An increase in blood pressure above the standard threshold is categorized as hypertension. A few variables that are such as age, genetics, unhealthy habits, and foods high in fat, salt, or cholesterol, may impact the appearance of hypertension. Increases in blood triglycerides and cholesterol may occur due to hypertension. Atherosclerotic plaque, produced by excess cholesterol and triglycerides interacting with other chemicals and depositing in the arteries, causes the heart to work harder to deliver blood to all tissues. This research aims to determine how hypertension patients at the UPTD Regional Health Laboratory in Jambi City react to their triglyceride and cholesterol levels. This study used an analytical descriptive research methodology. In this study, 50 hypertension patients were asked about triglyceride and cholesterol levels measured using the GPO-PAP method and the CHOD-PAP enzymatic colorimetric cholesterol test method. According to the study's results, hypertension patients had a mean cholesterol level of 275.76 mg/dl and a mean triglyceride level of 236.64 mg/dl. Statistical analyses showed a strong correlation (p<0.05) between triglycerides and cholesterol in hypertension patients at the UPTD Regional Health Laboratory in Jambi City. Patients with hypertension need to maintain a healthy lifestyle and get periodic tests for triglycerides and cholesterol to reduce the risk of problems.